2021
DOI: 10.1021/acsami.1c09619
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Under Pressure: The Role of Solvent, Crystal Size, and Morphology During Pelletization of Metal–Organic Frameworks

Abstract: As metal–organic frameworks (MOFs) gain traction for applications, such as hydrogen storage, it is essential to form the as-synthesized powder materials into shaped bodies with high packing densities to maximize their volumetric performance. Mechanical compaction, which involves compressing the materials at high pressure, has been reported to yield high monolith density but often results in a significant loss in accessible porosity. Herein, we sought to systematically control (1) crystal size, (2) solvation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…This finding suggests that Ce-based and bimetallic MOF-808 possess much worse mechanical stabilities compared to Zr-MOF-808 and may become amorphous MOF-derived materials after the high-pressure pelletizing process; this finding is in part supported by recent literature, which reported that Ce-MOF possesses worse mechanical stability than its Zr-based analogues . Though a recent study suggested that the solvation of MOFs can prevent the structural damage during the pelletizing process, for Ce-MOF-808 here, we found that pelletizing the powder fully solvated with acetone under 115 MPa still resulted in the complete loss of crystallinity, and the solvated MOF failed to form the intact pellet when we further reduced the pelletizing pressure to 0.1 ton, i.e ., 23 MPa. Thus, to resolve this issue, the dry samples of all MOF-808 samples were pelletized under a low pressure of 23 MPa, and the XRD patterns of the obtained pellets are shown in Figure b.…”
Section: Resultssupporting
confidence: 83%
“…This finding suggests that Ce-based and bimetallic MOF-808 possess much worse mechanical stabilities compared to Zr-MOF-808 and may become amorphous MOF-derived materials after the high-pressure pelletizing process; this finding is in part supported by recent literature, which reported that Ce-MOF possesses worse mechanical stability than its Zr-based analogues . Though a recent study suggested that the solvation of MOFs can prevent the structural damage during the pelletizing process, for Ce-MOF-808 here, we found that pelletizing the powder fully solvated with acetone under 115 MPa still resulted in the complete loss of crystallinity, and the solvated MOF failed to form the intact pellet when we further reduced the pelletizing pressure to 0.1 ton, i.e ., 23 MPa. Thus, to resolve this issue, the dry samples of all MOF-808 samples were pelletized under a low pressure of 23 MPa, and the XRD patterns of the obtained pellets are shown in Figure b.…”
Section: Resultssupporting
confidence: 83%
“…Pd@MIL-101 composites thus result to be better candidates, compared to pristine MIL-101, for post-synthetic modification involving compression. Indeed, the shaping and densification of loose MOFs powders in pellets, beads or monoliths, which is necessary before any application, usually involves loadings up to several tons corresponding to pressures of hundreds of MPa, 47,48 i.e. values compatible with the pressure range explored in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Pd@MIL-101 composites thus result to be better candidates, compared to pristine MIL-101, for postsynthetic modification involving compression. Indeed, the shaping and densification of loose MOF powders in pellets, beads, or monoliths, which is necessary before any application, usually involves loadings up to several tons corresponding to pressures of hundreds of MPa, , that is, values compatible with the pressure range explored in the present study. Therefore, combining the incorporation of functional nanomaterials in the framework with densification processing could become a successful strategy to further improve the MOF performances for applications.…”
Section: Resultsmentioning
confidence: 99%
“…62 However, despite appealing activities reported here with MOF-808-DPPB-Rh catalysts for liquid phase application, the transfer from triphasic batch to fixed-bed gas-phase reactor require the formulation and the shaping of the MOF catalysts into adequate bodies which are not trivial and are still under investigations. [63][64][65][66] Molecular-level comparison of the two MOF-808-DPPB-Rh systems. To get insight into the evolution of the molecular Rh active site within the MOF, diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy and PDF analysis, in combination with computational models as structural references, evidence that the two catalysts from the two Rh precursors show similar spectroscopic fingerprints after exposure to CO/H2/C2H4 mixture.…”
Section: Table 2 Catalytic Activity Of Mofmentioning
confidence: 99%